Дослідження антонімічних відношень у психолінгвістичному експерименті - Литвин, Оксана Леонідівна; Lytvyn, O. L. (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті викладено методику проведення та результати психолінгвістичного експерименту, скерованого на виявлення структури та наповнення лінгвістичної категорії антонімії в англійській мові. Респондентами виступили 70 лінгвістів (наукові співробітники, викладачі університетів та коледжів), носії англійської мови, з різних країн. У ході експерименту опитувані мали визначити, якою мірою певні антонімічні пари (20 пар) репрезентують явище лексичної антонімії, оцінюючи за шкалою «0–3». Матеріали для експерименту були відібрані з англомовних монографій, підручників та лінгвістичних енциклопедій. Аналіз результатів експери¬менту дав змогу окреслити центральну зону розглядуваної категорії, тобто виокремити антонімічні пари, які, на думку опитаних лінгвістів, найкраще репрезентують відношення лексичної антонімії. У ході експерименту виявлено, що оцінка їхньої репрезентативності майже не залежить від рангу в лінгвістичних працях. Дані екс¬перименту дають можливість стверджувати, що більшість антонімічних пар, поданих як приклади в лінгвістич¬них працях, є типовими у категорії антонімії і складають її центральну зону. This article presents the methodology and the results of a psycholinguistic experiment which was conducted for the purpose of determining the structure and the content of the linguistic category of antonymy in the English language. All of the 70 participants in the experiment (scholars in linguistics, university and college professors) are native speakers of English originating from a number of different English-speaking countries. In this experiment, the respondents were to evaluate and compare the extent to which a selection of twenty antonymous pairs can be considered to represent the phenomenon of lexical antonymy, using a scale of 0 to 3 points. The material for the experiment was selected from monographs, textbooks and linguistic encyclopedias written in English. Analysing the results of the experiment, we were able to identify the central zone of the category under investigation – the antonymous pairs which, in the opinion of the linguists consulted, provide the best representation of the relation referred to as lexical antonymy. The experiment showed that representativeness rating of the antonymous pairs does not correspond directly to their ranking in the linguistic works. The data produced by the experiment makes it possible for us to conclude that most of the antonymous pairs which are presented as illustrative examples in linguistic works are typical representatives of the lexical category of antonymy and constitute its central zone.
Study of Antonymic Relations as Evidenced in a Psycholinguistic Experiment
Keywords: психолінгвістичний експеримент; psycholinguistic experiment; лінгвістична категорія; linguistic category; структура категорії; structure of the category